1969
DOI: 10.1128/jb.100.1.140-148.1969
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Partial Characterization of an Immunogenic Moiety Obtained fromSalmonella typhimurium

Abstract: Ribosomal preparations obtained from Salmonella typhimurium by differential centrifugation and sodium dodecyl sulfate (SDS) treatment of the bacillary lysate were found to be immunogenic in F1 hybrid (C,H/HeJ x DBA/2J) and albino Swiss mice, as determined by progressive host survival. The immunity obtained was independent of the need for adjuvant and dependent on the dosage of immunogen given. Immunizations with the ribosomal preparations induced an immune response comparable to that obtained by vaccination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
51
1

Year Published

1972
1972
1991
1991

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 32 publications
7
51
1
Order By: Relevance
“…In more recent work (46), they have further suggested that the immunogenic activity of the fractions may be associated with one particular species of nucleic acid. 1 Preliminary results of this investigation were presented at the Annual Meeting of the American Society for Microbiology, Minneapolis, Minn., 2-7 May 1971. Immunization with bacterial ribosomal preparations has also been found to be an effective means of prophylaxis for infections with Staphylococcus aureus (41), Pseudomonas aeruginosa (40), Diplococcus pneumoniae (30), and Salmonella typhimurium (35). The immunogenic fractions of these organisms consist of approximately 60% RNA, 30% protein, and 10%7, "contaminant" material on a dry weight basis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent work (46), they have further suggested that the immunogenic activity of the fractions may be associated with one particular species of nucleic acid. 1 Preliminary results of this investigation were presented at the Annual Meeting of the American Society for Microbiology, Minneapolis, Minn., 2-7 May 1971. Immunization with bacterial ribosomal preparations has also been found to be an effective means of prophylaxis for infections with Staphylococcus aureus (41), Pseudomonas aeruginosa (40), Diplococcus pneumoniae (30), and Salmonella typhimurium (35). The immunogenic fractions of these organisms consist of approximately 60% RNA, 30% protein, and 10%7, "contaminant" material on a dry weight basis.…”
mentioning
confidence: 99%
“…Preparation of crude RNA fractions. The procedure employed for the preparation of the immunogenic RNA fractions was that described previously with modification (35,36). An 8-liter broth culture of S. typhimurium SR-11 in midto late-log growth was harvested by continuous-flow centrifugation at 40,000 X g in a Sorvall refrigerated high-speed centrifuge.…”
mentioning
confidence: 99%
“…Preparation of bacterial cultures for nucleic acid extractions. The techniques for culturing, harvesting, and rupturing the virulent S. typhimurium were those of Venneman and Bigley (18) with the following exceptions. A 0.01 M phosphate buffer, pH 7.1, containing 4 X 10-4% polyvinyl sulfate (20) was used in the washing and harvesting of the bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…Both RNA and protein moieties appeared to be necessary components of the effective immunogen. Venneman and Bigley (18) and Venneman et al (19) have shown that both a ribosomal subfraction from Salmonella typhimurium SR-1I and its subunits are effective immunogens in stimulat-ing immunity to lethal salmonellosis in mice. They also observed that an ethanol-precipitated, crude RNA fraction of the ribosomal preparations induced protective immunity comparable to that developed after immunization with the whole ribosomal fraction.…”
mentioning
confidence: 99%
“…A number of studies on salmonella ribosomal vaccines have been reported since Venneman and Bigley [1] demonstrated the immunogenicity of a subcellular, ribonucleic acid preparation of Salmonella typhimurium. Many investigators indicated that the efficacy of salmonella ribosomal vaccines varies with mouse strains [2], and that contaminating lipopolysaccharide (LPS) exerted the major effect [3,4].…”
Section: Introductionmentioning
confidence: 99%